(untitled) (Nigerian Journal of Technology, 2025)
Effect of zinc oxide (ZnO) nanoparticles (NPs), manganese dioxide (MnO2) NPs and their blends on the yield and quality of bioethanol produced from co-fermentation of banana and potato wastes has been investigated. Thus, in this study, ZnO, MnO2 NPs and their novel blend were synthesized, characterized and employed as additives to the fermentation processes, and their effects on the yield and quality of bioethanol produced from various blends of the organic wastes were evaluated. Potato peels (PP) and banana peels (BP) were collected and prepared for sample characterization. Prepared samples were then pretreated using acid pretreatment method before enzymatic hydrolysis, co-fermentation and products analyses were carried out. Series of experiments were carried out using the feedstock blends: 100 wt.%BP: 0 wt.%PP, 30 wt. %BP: 70 wt.%PP, 70wt.%BP: 30 wt.%PP, 50 wt. %BP: 50 wt.%PP and 0 wt. %BP: 100 wt.%PP. The ZnO, MnO2 and ZnO+MnO2 NPs were added to the feedstock blends, and the blends without nanoparticles served as control samples. Study results unveiled that the highest yield of bioethanol (29.72g/l) was obtained from the sample blend, 100wt%BP + 0wt.%PP treated with ZnO NPs, and this was followed by 28.52g/l of bioethanol obtained from 50wt.%BP + 50wt.%PP sample blend treated with ZnO and ZnO +MnO2 NPs. It was also observed that the amount of bioethanol produced from addition of ZnO NPs to samples is higher than those produced from control samples as well as from samples treated with MnO2 and ZnO +MnO2 NPs. This may be because ZnO acts as a better catalyst, positively enhancing the enzymatic activity which accelerates the conversion of sugars into ethanol than MnO2 NPs. Product analysis results further unveiled the effect of the nanoparticles on the quality of bioethanol produced. Results of this study could enhance sustainability and economic viability of bioethanol production from organic wastes using nanoparticles.